Analysis of Factors Influencing Customers Decisions in Taking Murabahah Financing at Bank Muamalat Indonesia - Mutiara Rahmah; Muhlis Muhlis; Kartika Marella Vanni (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - To study in more depth by identifying the factors that influence customer decisions in taking murabahah financing at Bank Muamalat Indonesia. Methods - The methods used are quantitative research with data collection through distributing questionnaires. Method - The method used in this study is qualitative, which is a research approach used to understand social phenomena in depth, from a complex and contextual perspective. In qualitative research, data is collected in a way that allows researchers to explore the feelings, thoughts, and experiences of respondents, and to understand the context in which the phenomenon occurs. Result - The results obtained are that the margin variables, customer knowledge and financing procedures, both partially and simultaneously, have a significant positive influence on customer decisions in taking murabahah financing at Bank Muamalat Indonesia. Implication - By understanding the factors that influence customer decisions, banks can expand the inclusion of sharia financing to unreached groups, especially in areas with low sharia financial literacy. Efficient and targeted murabahah financing can encourage the growth of the real sector and support an economy based on Islamic ethics. Originality - Specifically examines customer decisions on murabahah products at Bank Muamalat Indonesia as the first Islamic bank in Indonesia using a combination of relevant and contextual variables combined with the use of actual primary data based on direct customer experience. With the hope of filling the gap in previous research that has not linked these factors comprehensively in Islamic financial institutions. Keywords:                     Murabahah Financing, Margin, Customer Knowledge, Financing Procedure.